FACTORS INFLUENCING FRAUD WHISTLEBLOWING - Hendra Raza; Fawati Hushuwar Batubara; Rico Nur Ilham (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to look at the effects of professional commitment, organizational commitment, locus of control, ethical orientation, and anticipatory socialization on fraud whistleblowing in the case of Himatansi (accounting students association) and non-Himatansi students of Malikussaleh University. In addition, this study also aims to see differences in the levels of professional commitment, organizational commitment, locus of control, ethical orientation, and anticipatory socialization between Himatansi and non-Himatansi students of Malikussaleh University. This study employed Slovin’s formula for sampling, with a critical value or accuracy limit of 0.1. As a result, a sample of 70 was extracted from a total population of 221 students. This study also used multiple regression analysis techniques and performed hypothesis testing using SPSS program. The results show that professional commitment and locus of control had significant effects on fraud whistleblowing, while organizational commitment, ethical orientation, and anticipatory socialization did not. In addition, a difference was found in the level of professional commitment, but there were no differences found in the level of organizational commitment, locus of control, ethical orientation, and anticipatory socialization. Lastly, there was a significant difference between Bidikmisi and non-Bidikmisi students of Malikussaleh University.